Macro economics: Liquidity, Solvency, and External Factor as Determinant of Government Bond Index Yield (INDOBEXGB) with The Vector Error Correction Model (VECM) - Nurlia Rahmatika; Muhamad Noer Fachmi (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2020)
The purpose of this research to analysis of several variables such as macroeconomics variables and volatility index to yield on government bond index. The macroeconomic indicators studied are consumer price index, BI rate, money supply, foreign reserve, exchange rate, Indonesia total debt, and external factor volatility index S&P 500. The period of this research was conducted using secondary data from January 2012 until December 2017. This research use Vector Error Correction Model (VECM) method because there is cointegration between variables, indicated by Trace Statistic and Max-Eigenvalue statistic which is bigger than Critical Value. The result of analysis shows that BI rate, money supply, Indonesia total debt, and volatility index S&P 500 give positive influence to yield government bond index INDOBEXGB, while consumer price index, foreign reserve, and exchange rate give negative effect to yield government bond index INDOBEXGB. The policy implication on the yield of state bonds is useful for the government as the economic authorities to determine the amount of bonds to issued and front loaded or wait and see strategy in issuing bonds. For corporate issuer is useful for reference in determining the cost of fund for corporate bonds issued.